The Identification of Students’ Misconceptions in Mathematical Induction - Sikky El Walida; Siti Nurul Hasana (Journal of Education and Learning Mathematics Research (JELMaR), 2020)
This study was conducted to identify the types of students’ misconception, factors that cause students’ misconception, and to describe the problem-solving of students’ misconception in mathematical induction. The subjects of this study were 30 junior students of Mathematics Department of Faculty of Teacher Training and Education of Universitas Islam Malang, who take Real Analysis I course. With respects to the students’ performance, the results of the study showed that most students had difficulty in interpreting letter, notation, generalization, and rules application. The factors that influence the students’ algebra misconceptions in mathematical induction was the students’ lack of ability, the lack of willingness that hinder the students’ cognitive development, and the lack of learning motivation. In order to solve these problems, the researcher proposed a method called guided discovery method.